Upregulation of muscarinic receptors by long-term nitric oxide inhibition in the rat ileum - Bricola, A. A.; Teixeira, S. A.; De Luca, I. M.; Muscara, M. N.; Abdala, F. M.; Porto, C. S.; Zanesco, A.; Antunes, E.; De Nucci, G. (Blackwell Publishing Asia, 2003)
1. The aim of the present study was to examine the effects of long-term nitric oxide (NO) blockade on contractions of the rat ileum induced by muscarinic agonists.2. Male Wistar rats received the NO synthesis inhibitor N (G) -nitro-l-arginine methyl ester (l-NAME; 20 mg/rat per day) in drinking water for 7, 15, 30 and 60 days. Concentration-responses curves to methacholine and carbachol were obtained and pEC(50) values were calculated. Saturation binding assays were performed in membranes prepared from rat ileum after 60 days of l-NAME treatment and the dissociation constant (K-D ) and maximal number of binding sites (B-max ) were determined by Scatchard analysis.3. The NO synthase activity of the ileum was markedly reduced in all l-NAME-treated groups. At 60 days after l-NAME treatment, a significant increase in the potency of methacholine (fourfold) and carbachol (threefold) was observed. In binding studies, we found a significant increase in B-max for [(3) H]-quinuclidinyl benzilate of approximately 57% in the l-NAME treated group without any significant change in K-D values. The contractile response to methacholine was not modified by the soluble guanylate cyclase inhibitor 1H-[1,2,4]oxadiazolo-[4,3-a]quinoxalin-1-one (3 mumol/L). No morphological alterations in the rat ileum were observed in l-NAME-treated rats.4. Our findings suggest that treatment with l-NAME for 60 days induces a marked increase in the potency of methacholine and carbachol, as well as an increase in receptor number in the rat ileum.
Keywords: contractile response; nitric oxide synthase; N-G-nitro-L-arginine methyl ester; non-adrenergic non-cholinergic fibres